2020
DOI: 10.3390/rs12213544
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Modeling of the Complex Dielectric Constant of Bound Water with Application in Soil Microwave Remote Sensing

Abstract: Complex dielectric constant (CDC) of bound water determines the accuracy of the complex dielectric constant of wet soil. According to electrical double-layer structure and dielectric properties, the bound water on clay particle surface is divided into strongly bound water and weakly bound water. Based on this classification, models for the complex dielectric constants of bound water and soil are established taking into consideration factors such as temperature, moisture, texture, and microwave frequency. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…The material under this investigation is a mixture of paper and water. The losses due to a proportion of water in the paper can be modeled using similar techniques described in [10] [11] to obtain the complex dielectric constant (CDC) of the mixture. For accuracy, the model must be compared with the experimental data which are not available at this stage.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…The material under this investigation is a mixture of paper and water. The losses due to a proportion of water in the paper can be modeled using similar techniques described in [10] [11] to obtain the complex dielectric constant (CDC) of the mixture. For accuracy, the model must be compared with the experimental data which are not available at this stage.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…The Stern-Gouy electrical double-layer theory is used to describe the microscopic structure at the solid surface [32]. The outer enamel layer (less than 1 μm from the anatomical surface) is most likely a non-stoichiometric apatite.…”
Section: Surface Properties Of Enamelmentioning
confidence: 99%
“…For these saltwater-related parameters, many studies have already provided theoretical and empirical approaches for their calculation [37][38][39]. Specifically, the high-frequency extreme value of the dielectric constant of saltwater (ε sw∞ ) is regarded as having an identical value to the parameters of free water and is considered to have a specific value of 4.9 [44]. The Stogryn model gives semi-empirical formulas to acquire ε sw0 τ sw and σ sw [39].…”
Section: Saline-soil Dielectric Constant Modelmentioning
confidence: 99%
“…Many studies have already demonstrated that salinity significantly influences the imaginary part of the saltwater dielectric constant [44,45]. However, the existing models have large errors when simulating this variable, especially for soil with high water and salinity contents [37].…”
Section: Saline-soil Dielectric Constant Modelmentioning
confidence: 99%